Get Answers to all your Questions

header-bg qa

The solution of the equation 3 sinh x - cosh x =1 , is

Answers (1)


Solution:     We have ,     3sinh x-cosh x=1

                  Rightarrow         3(frace^x-e^-x2)-(frace^x+e^-x2)=1

                   Rightarrow                          e^x-(frac2e^x)=1

                  Rightarrow             t^2-t-2=0,   where   e^x=t.

                   Now ,        t
eq-1           ,    e^x

                   	herefore                e^x=2Rightarrow x=ln 2 .   

Posted by

Deependra Verma

View full answer